The Role of Risk Management in Enhancing Cybersecurity for Small and Medium Enterprises (SMEs) in Saudi Arabia “Applied Study” (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aimed to evaluate and improve cyber risk management in small and medium enterprises in the Kingdom of Saudi Arabia. The study relied on the descriptive, analytical and inductive approach, using data collection tools such as questionnaires, interviews and case studies. The most prominent results were weak level of use of information technology among 50% of employees. Shipping and delivery procedures policy is the most used at 33%. Antivirus software is the most used security technology at 40%. Fake audio and video attacks represent the biggest obstacle to cyber risk management at 30%. 50% of employees are aware of cyber risks. There is a strong correlation (89%) between employee awareness and cyber risk management. Key recommendations include raising awareness, developing comprehensive policies, conducting periodic risk assessments, investing in modern technologies, building a strong security culture, and providing qualified human resources.
Keywords: Risk Management; Cybersecurity; Small and Medium Enterprises